(untitled) (Al-Qamar, 2023)
This paper is a descriptive analysis of the idea of slavery, under the case study of Hanafi School of Islamic jurisprudence. Although world has moved on a lot from the slavery as an institution but slavery has transformed itself into new frames whether it is bonded labor or the human trafficking. In this new context the question about the place of slavery in Islam becomes more important and critical to be addressed. This paper argues that Islam as a religion was introduced in the Arab region where slavery was much abused and victimized but Islam upgraded the social status of salves and intensely focused on kind behavior with them. This research also maintains that Islam as a religion gradually developed a societal structure that can sustain without the institution of slavery. Qualitative methodology along with primary sources has been used in this research.